UNDERSTANDING THE IMPACT OF DIGITAL TRANSFORMATION ON AN ADVERTISING CAMPAIGN - GRYNKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the phenomenon of digital transformation, highlights its elements, directions and mechanisms of influence in connection with various spheres of economic activity. The main elements and processes of the advertising campaign are defined. Correspondence of the impact of certain components of digital transformation on the components of the advertising campaign has been established.Three spheres of impact of digital transformation on the enterprise are identified, namely: customer experience, operational processes, business models. It is noted that within the framework of digital transformation, a pattern of formation and organization of a digital business ecosystem is distinguished: an internal environment formed as a network of interdependent elements that interact with the help of digital technologies. Therefore, advertising activity within the framework of such a system cannot be isolated, instead it is closely integrated into the processes of value creation and sales. As part of the study of the impact of digital transformation on organizations, it is proposed to divide this impact by the strength of focus on processes and the breadth of coverage of this impact. The following groups are defined: separate adaptation, technological influence, integral coevolution, systemic displacement.The conducted analysis allows us to state that the phenomenon of digital transformation is comprehensive, touches all elements of the organization and represents revolutionary changes in its activities. Accordingly, the advertising campaign is also the object of this influence. The analysis of the direction of influence of digital transformation on the advertising campaign and the categorization of the directions of this influence made it possible to establish that the variety of innovative technologies has numerous effects on the elements of the advertising campaign, their transformation and the definition of their new forms. The most important thing is the change in the organizational approach to the advertising campaign, in particular, the transition from linear processes to network ecosystems, in which all elements are connected by one network and constantly interact with each other. This can be a competitive advantage of the enterprise in the market.
Keywords: digitization; advertising campaign; business model; digital ecosystem; marketplace